Analysis of the Mediating Effect of Risk Perception on the Relationship Between Time Perception and Mental Health of College Students During the COVID-19 Epidemic - Cao, Hua; Zhang, Hui Wen; Yang, Ling; Li, Ling; Wang, Jun Zhi; Zada, Bakht; Li, Min Xiao; Liu, Wei Jian; Su, Ting Hong; Zhao, Yu (Frontiers in Psychiatry, 2021)
Background: COVID-19 has had a broad impact on the mental health of college students. This study aims to explore the relationship between time perception, risk perception, and mental health of college students during COVID-19 through questionnaire survey Subjects: 1218 college students who studied online during the COVID-19 epidemic were selected, including 449 male and 769 female students. Methods: Time Perception Scale, Risk Perception Scale, and SCL-90 were used to investigate among them by correlation analysis. Results: During the COVID-19 period, mental health problems of college students were widespread, and 65.93% of college students reported moderate to severe mental health problems. The correlation analysis showed that college students' risk perception, time perception, and mental health were significantly related. Risk perception played a partial mediating role between present enjoyment and mental health, and risk perception played a partial mediating role between future time perception and mental health. Conclusion: In the case of a sudden public crisis, we should pay close attention to the mental health of college students, adjust their attitude towards the present and the future, and pay attention to their perception of risk to improve their mental health level under the crisis.